Embodiment of Parental Love Through the Medium of Wooden Matches in Expression Photography - Ichsan Saputra; Sulaiman Juned; Sahrul Nazar (Universitas Negeri Medan, 2024)
This photographic work raises the theme of parental love through the medium of wooden matches in expression photography. This work focuses on life experiences, the daily activities of the creator while he was born and grew up full of love from his parents in Aceh. The theory of ideas that the creator uses in creating this work of Expression photography is in the form of Expression Photography, Composition, Semiotics and Lighting. This creation method also involves experimentation. The creative concepts and ideas displayed in this photo work are a reflection of the creator's daily life. The main object in making this work is a miniature person created from wooden matches. This work is inspired by the author's life story of the sincere love of his parents, as well as daily life activities that the author has experienced and felt. Rooted in a deep narrative of parental love, the project captures the essence of familial warmth and affection, depicting miniature wooden matchsticks involved in everyday activities as symbolic representations of the human experience. Each photo encapsulates a narrative of parental love and familial bonds, visually depicting moments of tenderness, joy and nurturing care. In